Anakinra for colchicine refractory familial Mediterranean fever: a cohort of 44 patients. (2nd December 2020) - Marko, Limor; Shemer, Asaf; Lidar, Merav; Grossman, Chagai; Druyan, Amit; Livneh, Avi; Kivity, Shaye
Abstract: Objective: FMF is an autoinflammatory disease of genetic origin. Colchicine is the mainstay of treatment for the prevention of attacks and long-term complications but 5–10% of FMF patients are resistant to colchicine therapy. The aim of our study was to investigate the real-life safety and efficacy of anakinra in a cohort of patients with colchicine-resistant FMF. Methods: In this retrospective study, patients treated with anakinra for colchicine-resistant FMF between 2010 and 2018 were identified using the computerized database of Sheba Medical Center and enrolled in the study. Data from structured clinical files were analysed to evaluate the efficacy and safety outcomes. To assess efficacy, we used the Global Assessment Score (GAS), a measure comprised of three different domains: number of attacks per month, duration of attacks and number of sites involved in the attacks. Reported adverse events were compiled. Results: A total of 44 patients (24 female) were treated with anakinra. Of these patients, 75% were homozygous for the M649V mutation. The mean duration of treatment was 18 months. The GAS decreased significantly from 6.6 (IQR 5.3–7.8) before treatment to 2 (IQR 0–4.2) while on treatment ( P  < 0.001). During anakinra treatment, six hospitalizations were reported (three due to related adverse effects). In addition, 11 patients suffered from injection site reactions (5 ceased treatment). Twelve patients reported mild side effects. Conclusion: Treatment with anakinra is beneficial for the majority of colchicine-resistant FMF patients and is relatively safe.